Analisis Niat Pembelian Konsumen terhadap Sayuran Organik di Indonesia (Integrasi Teori Perilaku Terencana dan Teori Nilai Konsumsi) - Dwi Putri Sunaryanti; Irzaq Galuh Pranata; Akbar Maulana Akbar Maulana (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2025)
Organic vegetables are highly sought-after products due to their reputation for being free from harmful chemicals and not using pesticides or synthetic fertilizers in their cultivation process. Although organic vegetables are considered healthier and more environmentally friendly, the purchase rate by Indonesian consumers is still relatively low. One of the factors that influences the low level of purchase of a product or service by consumers in Indonesia is purchase intention. This study aimed to examine the purchase intention of Indonesian consumers using the theory of planned behavior and the theory of consumption value. The lack of integration between these two theories in analyzing the purchase intention of organic vegetables in previous studies presents a new opportunity to combine both theories for a more comprehensive understanding of the factors influencing the purchase intention of organic vegetables in Indonesia. Data collection was conducted from June to August 2023 using accidental sampling by distributing questionnaires via Google Form, which yielded 365 respondents, all supermarket visitors in the Jabodetabek area. The collected data were then analyzed using SPSS 26 with multiple linear regression analysis. The study's results indicated that attitudes toward organic vegetables, perceived behavioral control, functional value, and novelty value significantly influence the purchase intention of organic vegetables. Meanwhile, subjective norms, emotional value, social value, and conditional value were found to have no significant impact on the purchase intention of organic vegetables.